2012
DOI: 10.3389/fnmol.2012.00014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GSK3 by lithium, from single molecules to signaling networks

Abstract: For more than 60 years, the mood stabilizer lithium has been used alone or in combination for the treatment of bipolar disorder, schizophrenia, depression, and other mental illnesses. Despite this long history, the molecular mechanisms trough which lithium regulates behavior are still poorly understood. Among several targets, lithium has been shown to directly inhibit glycogen synthase kinase 3 alpha and beta (GSK3α and GSK3β). However in vivo, lithium also inhibits GSK3 by regulating other mechanisms like the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
194
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(216 citation statements)
references
References 86 publications
4
194
0
8
Order By: Relevance
“…Lithium also decreases the expression of pro-inflammatory cyclooxygenase-2 and inducible nitric oxide synthase. Reports also suggest that LiCl may be inhibiting GSK-3β via phosphorylation of AKT (Freland and Beaulieu, 2012). We have previously reported that AKT phosphorylation is impaired in DCs from aged subjects (Agrawal et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…Lithium also decreases the expression of pro-inflammatory cyclooxygenase-2 and inducible nitric oxide synthase. Reports also suggest that LiCl may be inhibiting GSK-3β via phosphorylation of AKT (Freland and Beaulieu, 2012). We have previously reported that AKT phosphorylation is impaired in DCs from aged subjects (Agrawal et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that lithium can inhibit GSK activity both directly or indirectly by increasing inhibitory phosphorylation with unclear relativity between these modes of inhibition 24 . However, recent literatures indicated that lithium regulates GSK-3 not only directly but also through more complex network affecting multiple molecular targets at a time 25 , which complicates its effect on GSK-3β even more on top of the bifunctional role of GSK-3β in cell apoptosis 26 . On the other hand, in our study, lithium was given before MIRI, which cancelled the protective effects of myocardial ischemic post-conditioning.…”
Section: ■ Discussionmentioning
confidence: 99%
“…6h. Lithium ions dissociated from acetoacetate lithium are biologically active and inhibit the function of GSK-3␣/␤ and other key kinases (COX, Arrestin-2, CaMK1, PHK, CHK2, NEK6, and IKK␥), which play important roles in regulating cell proliferation (71,72). Therefore, we treated C2C12 cells with acetoacetate sodium to rule out the possibility that cell proliferation promoted by acetoacetate lithium was due to the activity of lithium effect rather than acetoacetate itself.…”
Section: Discussionmentioning
confidence: 99%